1997
DOI: 10.1021/cm960606f
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of a Material of Composition BiP (Bismuth Phosphide) and Other Intergroup 15 Element Phases

Abstract: The reaction between equimolar quantities of BiCl3 and the silylphosphine P(SiMe3)3 in toluene or THF (tetrahydrofuran) solution affords a black precipitate with the composition of bismuth phosphide, BiP, which has been examined by EDXA, SEM, XPS, powder XRD, solid-state 31P NMR spectroscopy, and elemental analysis. Alternative possible routes to BiP involving the reactions between Na3P and BiCl3 and between Bi(NMe2)3 and P(SiMe3)3 have also been investigated, both of which afford black powders of composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…The compounds were chosen to cover a broad range of electronegativity variation; note that AsP, BiAs and SbAs solids have been reported experimentally. 79 Since the phase diagram is constructed with two arsenics in mind, we must readjust our results to account for the difference in the atomic size and mass of the diatomic compounds from elemental arsenic. In view of our results for mixed-pnictogen trimers from the preceding Section, we used the ionic radii as the rescaling factor for the length.…”
Section: Hierarchy Of Chemical Interactions: the Solid Statementioning
confidence: 99%
“…The compounds were chosen to cover a broad range of electronegativity variation; note that AsP, BiAs and SbAs solids have been reported experimentally. 79 Since the phase diagram is constructed with two arsenics in mind, we must readjust our results to account for the difference in the atomic size and mass of the diatomic compounds from elemental arsenic. In view of our results for mixed-pnictogen trimers from the preceding Section, we used the ionic radii as the rescaling factor for the length.…”
Section: Hierarchy Of Chemical Interactions: the Solid Statementioning
confidence: 99%
“…[34][35][36] Thus, we envisaged to prepare Bi/P NPs under smoother conditions in order to control the nanosized Bi/P materials, avoiding the formation of bulk materials. 20 For this purpose, we selected the reaction applied by Allen and coworkers, 21 relying on R 3 Si-X elimination as a driving force and using stabilizers to control the growth of nanoparticles in order to prevent precipitation of bulk material (Scheme 1). We have previously proved that ligands such as CD or PPP allow nanoparticles stabilization by coordination at the metal surface, [37][38][39][40][41] while polymers such as PVP provide steric stabilization 5 for nanoparticles of different transition metals.…”
Section: Resultsmentioning
confidence: 99%
“…Following this strategy, Allen et al reported the formation of an insoluble black material at room temperature from the reaction of BiCl 3 with P(SiMe 3 ) 3 . 21 A range of analyses were carried out to characterize this material, including SEM, EDX, XRD, XPS, thermogravimetric analyses (TGA and DSC) as well as conductivity measurements. These analyses prompted the authors to propose the formation of amorphous hybrid "BiP" materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bismuth phosphide, BiP, is of interest in materials science as an isoelectronic analogue of PbS, a common semiconducting material. 64 Despite this, few examples of structurally characterised bismuth phosphide compounds have been reported in the literature (Figure 1.3), and the majority contain silyl-substituted phosphides. The…”
Section: Bismuth Phosphidesmentioning
confidence: 99%